Fault detection and tolerance of electrical machines in automotive applications - Buckley, Gary (2017)
This project explores the drive for further electrification in the automotive industry and the challenges that this brings. Specifically this thesis focuses on the demands of safety and reliability; highlighting the subtle difference between the two concepts, explaining how legislation is forcing designers to consider the ways in which a system could fail and requiring them to create methods to detect and safely handle these failures, many of which can never be completely eliminated by design.